Fostering Learners’ Skills to Self-Regulate Their Learning through Enquiry-Based Learning (2019)
Abstract: This actions research project aimed at exploring how Enquiry-Based Learning can foster 10th graders Self-Regulated Learning. To do this, students developed a travel guide following the process of selecting places, searching for information, writing a report, creating the travel guide and socialising their work orally. Activities were intended to promote Self-Regulated Learning skills such as setting objectives, self-monitoring learning, increasing responsibility. During this process, data was gathered implementing two students’ written reflections, a focus group and teacher’s journals. Analysis of data evidenced that learners were engaged when having appealing content to them and when making decisions, which arise motivation toward learning. Besides, data showed that having stages for the Enquiry-Based Learning task help finish it successfully.